BENTUK DAN GAYA BAHASA PANTUN PADA LIRIK LAGU CILOKAQ SASAK PEPAO-JANEPRIE DALAM ALBUM “SAQTEKANGEN” SERTA KAITANNYA DENGAN PEMBELAJARAN SASTRA - MUHAMMAD RIANDI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
There are two problems in this research. First, what is the form and style of the rhyme language in the lyrics of the song Cilokaq Sasak Pepao-Janeprie in the album “Saqtekangen”; second, how it relates to literary learning. The purpose of this study is to describe the form and style of the rhyme language in the lyrics of the song Cilokaq Sasak Pepao-Janeprie in the album "Saqtekangen" and its relation to literary learning. The method used in this study is a qualitative descriptive method. The technique of collecting data in this study used a listening and note-taking technique. The research subjects were four songs in the album "Saqtekangen" in the form of rhymes. After analyzing the data, it was found that (1) the form of the rhyme in the lyrics of the cilokaq song Sasak Pepao-Janeprie in the album "Saqtekangen" includes (a) the rhyme stanza consists of four lines in each stanza, (b) the number of words in each rhyme line consists of 4- 6 words or 8-12 syllables, and (c) the final rhyme of the rhyme with a cross pattern of a-b-a-b, (2) The use of rhyme language styles include: imagery, repetition, onomatopoeia hyperbole, irony, and litotes. (3) In relation to literature learning, the form and style of the rhyme language can be used as a medium for learning Indonesian Language and Literature which is innovative and creative at the junior high school level in accordance with the Basic Competence (KD) class VII semester I, namely identifying and studying the linguistic structure of local folk poetry (rhymes) that are read and heard. ABSTRAKAda dua permasalahan dalam penelitian ini. Pertama, bagaimana bentuk dan gaya bahasa pantun pada lirik  lagu Cilokaq Sasak Pepao-Janeprie dalam album “Saqtekangen”; kedua, bagaimana kaitannya dengan pembelajaran sastra. Tujuan penelitian ini adalah mendeskripsikan bentuk dan gaya bahasa pantun pada lirik lagu Cilokaq Sasak Pepao-Janeprie dalam album “Saqtekangen” serta kaitannya dengan pembelajaran sastra. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Teknik pengumpulan  data penelitian ini menggunakan teknik simak dan  catat. Subjek penelitian berupa empat buah lagu dalam album “Saqtekangen” yang berbentuk pantun. Setelah dilakukan analisis data ditemukan bahwa (1) Bentuk pantun pada lirik lagu cilokaq Sasak Pepao-Janeprie dalam album “Saqtekangen” meliputi (a) bait pantun terdiri atas empat larik pada setiap baitnya, (b) jumlah kata setiap larik pantun terdiri atas 4-6 kata atau 8-12 suku kata, dan (c) sajak akhir pantun dengan pola silang a-b-a-b, (2) Pemakaian gaya bahasa pantun meliputi: citraan (imagery), gaya bahasa repetisi, onomatope hiperbola, ironi, dan litotes. (3) Kaitannya dengan pembelajaran sastra, bentuk dan gaya bahasa pantun dapat dijadikan sebagai media pembelajaran Bahasa dan Sastra Indonesia yang inovatif dan kreatif pada jenjang SMP sesuai dengan Kompetensi Dasar (KD) kelas VII semester I, yaitu mengidentifikasi dan menelaah struktur kebahasaan puisi rakyat setempat (pantun) yang dibaca dan didengar.